The Role of Galectin-3 as a Biomarker of Osteoporosis and its Correlation with Bone Mineral Density - Mohammed , Noor Ulhuda G.; Al-Ghanny, Rand Jalal Abd; Al-Shawk, Refif Sabih; Abed, Baydaa Ahmed; Omran, Hussein Hatam (Iraqi Journal of Science, 2025)
This study investigates the potential link between serum levels of Galectin-3 (Gal-3) and bone health in postmenopausal women with osteoporosis. As Gal-3 is known to be expressed in bone cells and may influence bone remodeling, we aim to quantify serum Gal-3 levels in this population and examine its correlation with bone mineral density (BMD). In cross-sectional study, 45 postmenopausal women with OP and 45 healthy control group (HS), aged between 43-50 years, were registered. Patients and HS were categorized based on T score on dual-energy X-ray absorptiometry (DXA). Serum levels of calcium (Ca), Vitamin D3, and Gal-3 were measured both groups. The concentration of serum Gal-3 concentration was significantly increased in OP patients compared to the HS at (P< 0.001). Additionally, serum Gal-3 levels was positively correlate with BMD of the lumber spine (L1-L4) levels T score (r= 0.689, P=0.0001). Depended on the receiver operating characteristic curve (ROC), the criterion value of the Gal-3 was >11.905 ng/ml. In this study, OP postmenopausal women showed an increase in Gal-3, which is positively correlated with BMD of T-score on DXA. These results suggest a diagnostic role of Gal-3 in OP patients as well as its role in monitoring disease severity. Furthermore, this study is the first to assess serum Gal-3 concentration in patients with OP.